Strategic Management and Determinism - Bourgeois, L. J. (Academy of Management Review, 1984)
Contingency theories of management and economic theories of industrial organization both contribute to a mechanistic view of the strategic manager as “analyst.” In this view, the secret to managerial effectiveness is through the application of scientific laws or principles, be they “laws of organization” or “laws of the marketplace.” This paper argues for a view of strategic management as a creative activity and suggests a dialectic between free will and determinism in conceptualizations of strategic behavior.